The Rise of Insurgency in Ghana: Developing Fertile Grounds? - Emmanuel Siaw; Eric Elikem (Department of Government Studies Universitas Muhammadiyah Makassar, 2017)
Ghana can largely be described as a nation that has enjoyed relative peace and stability in a sub region bedevilled with violence and instability. However, this relative peace and stability has been overhyped leading to the neglect of certain conflict-prone variables that can prong the country into an insurgency; as has been experienced in many African countries. Analysing this from the perspective of the human needs theory, coupled with conducting a survey, the study finds that a sizeable number of Ghanaians are deficient in access to their basic needs. Consequently, it predisposes citizens to insurgent ideas and make them susceptible to insurgency. Thus the study recommends that the Ghanaian government must make provisions for achievement of basic needs, security presence and engagement of people in the governance system a priority to prevent the possibilities of the rise of insurgency in Ghana.